Physicochemical profile, amino acid, and flavors of probiotic yogurt with the addition of nano ZnO food grade - ARIEF, Irma Isnafia; ABIDIN, Zaenal; WULANDARI, Zakiah; BUDIMAN, Cahyo; ADIYOGA, Reza; KAMILA, Elfa Aida (Food Science and Technology, 2023)
Yogurt is a functional food produced through milk fermentation by yogurt bacteria. The addition of Lactiplantibacillus plantarum IIA-1A5 in the fermentation of yogurt yielding a yogurt probiotic has been shown to exhibit some functional properties. The effects of adding ZnO on the overall properties of the yogurt are unknown. This study aimed to investigate the effect of ZnO nanoparticles on the characteristics of conventional yogurt and yogurt probiotics. Four sets of yogurts were prepared: conventional yogurt, yogurt with added ZnO, yogurt probiotic, and yogurt probiotic with added ZnO. Most of the physicochemical properties of all yogurts were found to be comparable, except for fat and solid non-fat contents. The addition of ZnO increased the total lactic acid bacteria (LAB) in the yogurt, but it apparently inhibited L. plantarum IIA-1A5 as indicated by a lower LAB population in the yogurt probiotic with added ZnO compared with the yogurt probiotic without ZnO. However, the combination of L. plantarum IIA-1A5 and ZnO in yogurt significantly enhanced the DPPH inhibition activity. Additionally, the positive effects of ZnO were also observed on the total amino acid content, which significantly modulate the flavor compounds. This indicates that, overall, ZnO contributed to the better characteristics of yogurts.